The Tangible Benefits of Living Donation: Results of a Qualitative Study of Living Kidney Donors - Van Pilsum Rasmussen, Sarah E. (Transplant Direct, 2020)
The framework currently used for living kidney donor selection is based on estimation of acceptable donor risk, under the premise that benefits are only experienced by the recipient. However, some interdependent donors might experience tangible benefits from donation that cannot be considered in the current framework (ie, benefits experienced directly by the donor that improve their daily life, well-being, or livelihood). METHODS. We conducted semistructured interviews with 56 living kidney donors regarding benefits experienced from donation. Using a qualitative descriptive and constant comparative approach, themes were derived inductively from interview transcripts by 2 independent coders; differences in coding were reconciled by consensus. RESULTS. Of 56 participants, 30 were in interdependent relationships with their recipients (shared household and/or significant caregiving responsibilities). Tangible benefits identified by participants fell into 3 major categories: health and wellness benefits, time and financial benefits, and interpersonal benefits. Participants described motivations to donate a kidney based on a more nuanced understanding of the benefits of donation than accounted for by the current “acceptable risk” paradigm. DISCUSSION. Tangible benefits for interdependent donors may shift the “acceptable risk” paradigm (where no benefit is assumed) of kidney donor evaluation to a risk/benefit paradigm more consistent with other surgical decision-making.